2021
DOI: 10.1037/pri0000152
|View full text |Cite
|
Sign up to set email alerts
|

Shopping addiction: A brief review.

Abstract: Shopping is, and has long been, an important part of everyday life. It can easily take on the characteristics and symptoms of a behavioral addiction, such as preoccupation, mental appropriation as well as compulsiveness and loss of control. Thus, shopping addiction is becoming an increasingly important topic in research, especially in the context of the current pandemic . The pandemic has resulted in an increase in perceived risk factors. There is a plausible relationship between high perceived stress level al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
0
15
0
3
Order By: Relevance
“…Due to the growing digitalisation and use of the Internet, compulsive shopping has also been translated into the digital world, where, however, the purchasing behaviour occurs much more quickly, simultaneously, and in the absence of time and place restrictions (see Niedermoser et al [62] for a review). The aim of this study was the analysis of the psychological variables that may contribute to Compulsive Online Shopping, with a specific focus on the exploration of the role of Attachment Styles and the perception of Family Functioning as risk or protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing digitalisation and use of the Internet, compulsive shopping has also been translated into the digital world, where, however, the purchasing behaviour occurs much more quickly, simultaneously, and in the absence of time and place restrictions (see Niedermoser et al [62] for a review). The aim of this study was the analysis of the psychological variables that may contribute to Compulsive Online Shopping, with a specific focus on the exploration of the role of Attachment Styles and the perception of Family Functioning as risk or protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is appropriate because compulsive buying behavior is consistent with the major components of addiction, including salience, mood modification, conflict, tolerance, withdrawal, and relapse (Griffiths, 2005). The Bergen Shopping Addiction Scale has flexible COLLECTING BEHAVIORS DURING COVID-19 9 application because it is culturally and technologically neutral (Niedermoser et al, 2021). An adaption of the BSAS was made that focused on compulsive online shopping (Manchiraju, Sadachar, & Ridgway, 2017), however, that scale has been criticized for its redundancy since online shopping was already built into the BSAS (Griffiths et al, 2016).…”
Section: Measuring Purchasing Behaviorsmentioning
confidence: 99%
“…In clinical and field studies, it has been reported that 80–95% of the SA cases are women [ 20 , 25 ]. It is stated that women, youth, and people with psychological disorders [ 29 ] are particularly susceptible to problematic shopping behaviors [ 30 ]. However, in some studies there was no effect of gender on SA [ 23 , 31 ].…”
Section: Introductionmentioning
confidence: 99%